Developing Pragmatic Competence in an Instructed Setting: The Effectiveness of Pedagogical Intervention in Greek EFL Learners’ Request Production - Maria Economidou-Kogetsidis; Louiza Soteriadou; Loukia Taxitari (L2 Journal, 2018)
Using a short pedagogical intervention, a pretest-posttest design and baseline data (L1 English), the present study examined the effects of explicit instruction on the use of internal and external modification in requests among Greek Cypriot EFL learners. The findings revealed a complex picture with mixed results. Even though external modification showed some positive effects after the intervention, the study revealed no gains in relation to the overall use of internal modification as the learners’ overall use of lexical/phrasal mitigators deviated even more from NS usage after the pedagogical treatment. We argue that, in relation to the learners’ pragmalinguistic performance, the results seem to confirm the fact that surrounding factors such as the duration, quantity and quality of the pedagogical intervention play a complex role in accounting for such mixed findings. Results further showed that the way learners perceived social reality was not affected by the instructional treatment. Our findings suggest that learners’ sociopragmatic development may not be as easily amenable to teaching as pragmalinguistic development. The development of L2 sociopragmatic awareness seems to need both longer explicit pedagogical instruction and rich exposure to the target language environment.